The wild garden - Robinson, W.; Darke, Rick. (Portland : Timber Press, 2009)
Envisions a naturalistic approach to gardening. This book advocates the usage of hardy, locally adapted native and exotic plants that are arranged according to local growing conditions. It includes 112 color photographs by Rick Darke. It is intended for those who wish to know how we have arrived at an understanding of gardens.
Expansion of: 5th ed. 1895.
Includes bibliographical references (p. 349-350) and indexes.
boek
Keywords: Wild flower gardening; Wild flower gardening -- Great Britain; Wild flowers -- Great Britain; Exotic plants -- Great Britain